PENGUJIAN UNSUR LOGAM Co, OKSIDA MgO DAN Al2O3 PADA JENIS TANAH LIMONITE DENGAN MENGGUNAKAN METODE X-RAY FLOURESCENCE (XRF) - Wahab, Nurhikmah; Octavia, Rizka; Ramli, Irawati; Syaputra, Irfan (Jurnal Ilmiah Teknik Kimia, 2025)
Nickel Laterite Laterite is defined as one of the various products of the chemical weathering process. This research aims to analyze the content of the metal elements cobalt (Co), magnesium oxide (MgO), and aluminum oxide (Al₂O₃) in limonite soil types using the X-Ray Fluorescence (XRF) method. Limonite soil was chosen because it is rich in iron minerals and its potential to contain valuable element.The test results show variations in the concentrations of Co,MgO,and Al₂O₃ in the various limonite soil samples analyzed, namely an average of 0.07% cobalt (Co),an average of 5.18% of Magnesium Oxide, and an average of Aluminum Oxide of 7.34%. Differences in element levels are influenced by mineralogical composition, geological origin, and environmental conditions in the sampling area.This research makes an important contribution to understanding the distribution of important elements in limonite soils,which can be the basis for more effective management of mineral resources in the future